Adutos de Biginelli: síntese e estudo de inibição e de interação com a enzima urease - Taniris Cafiero Braga (2019)
Urease is an ureolytic enzyme present in the soil microbiota, plants and microorganisms and, in some cases, is considered a virulence factor. This enzyme partakes of the global nitrogen cycle and consequently contributes for the increase of CO2 and NH3 emission to environment. In crops, the urea is the main nitrogen fertilizer and the presence of urease decreases the nitrogen exploitation from volatilization. Therefore, urease inhibition is a strategy of medicinal and technological interest and this work aimed to synthesize Biginelli adducts with catalysts assistance and to evaluate the inhibition and molecular interaction between these adducts and urease from Canavalia enziformis. Looking to obtain Biginelli adducts were evaluated the use of niobium phosphate (NbOPO4) and 1-butyl-3-(4-sulfobutyl)-1H-imidazol-3-ium [BIMBS][Cl] as catalysts. NbOPO4 was stable at the evaluated calcination temperatures (400, 500 and 700 °C), presents amorphous structure, Brønsted acid sites and the concentration of total acids of 0.01 mol of acid sites g-1. After characterization of NbOPO4, the synthesis and characterization of [BIMBS][Cl] were described in 3 steps with 68% global yield. The compounds NbOPO4 and [BIMBS][Cl] showed catalytic activity in Biginelli reaction, however [BIMBS][Cl] presented better results in the optimized condition (71% yield). Then, using [BIMBS][Cl], 26 Biginelli's adducts it were synthetized with substituents containing electron donor or withdrawing groups on the aromatic ring with 4-92% yields. Then the urease inhibition was evaluated using 16 adducts of Biginelli via colorimetric method (indophenol model). Biginelli adducts inhibited the enzyme urease in the range of 10-47% and 3 thiourea derivatives with substituents 4-NO2, 2,3-OCH2O, 4-Br (AB7-S, AB9-S and AB11-S, respectively) showed inhibition of the same statistical significance as the hydroxyurea control. The 4 most active compounds and the thiourea and benzaldehyde derivative (ABS12-S) had the binding constants (Kb) determined by fluorescence. The thiourea derivatives with substituents 4-NO2 and 3-MeO (AB5-S and AB7-S, respectively) were the ones with the highest Kb and the interaction and inhibition mechanisms with urease enzyme were evaluated. The urease/Biginelli adducts complexes (AB5-S or AB7-S) were thermodynamically stable, competitive inhibitors and capable of performing non-unique interactions such as hydrophobic interactions or hydrogen and van der Walls interactions, respectively. The result of this work ahows that the presence of substituents in the Biginelli adducts modulates urease inhibition and interferes with the predominant interaction type at the enzyme/inhibitor complex.